2021
DOI: 10.4014/jmb.2106.06041
|View full text |Cite
|
Sign up to set email alerts
|

LINC01232 Promotes Gastric Cancer Proliferation through Interacting with EZH2 to Inhibit the Transcription of KLF2

Abstract: To clarify the role of long intergenic nonprotein-coding RNA 1232 (LINC01232) in the progression of gastric cancer and the potential mechanism, we analyzed the expression of LINC01232 in TCGA database using the GEPIA online tool, and the LINC01232 level in gastric cancer cell lines was detected by quantitative real time-polymerase chain reaction (qRT-PCR) as well. Cell proliferation assay, colony formation assay, transwell assay and tumor formation experiment in nude mice were conducted to observe the biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The results found that not only in data from TCGA but also in our selected samples, LINC01232 was upregulated in gastric cancer tissues compared to para-cancer tissues. These results were in accordance with reported studied by Liu et al 18 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results found that not only in data from TCGA but also in our selected samples, LINC01232 was upregulated in gastric cancer tissues compared to para-cancer tissues. These results were in accordance with reported studied by Liu et al 18 …”
Section: Discussionsupporting
confidence: 94%
“… 17 Recent study identified that LINC01232 promoted cell proliferation by interacting with EZH2 in gastric cancer. 18 However, the function of LINC01232 on metastasis and the possible mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The knockdown of LINC01232 is shown to suppress the proliferation of gastric-cancer cells both in vivo and in vitro. This finding suggests LINC01232’s potential as an effective therapeutic target for gastric cancer ( Table 2 ) [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLZF then recruits EZH2 to increase H3K27 trimethylation at the PDGFB promoter, suppressing its expression and subsequently downregulating PI3K/Akt signaling 157 . Two additional lncRNAs, LINC01232 and LINC00202 , were found to be upregulated in GC, and they interacted with EZH2, negatively regulating the expression of KLF2 , a zinc-finger transcription factor, through histone methylation 158 , 159 . Another oncogenic lncRNA, HOTAIR , promoted EMT by recruiting PRC2 to catalyze H3K27me3 at the CDH1 promoter in GC 160 .…”
Section: Interaction Between Ncrnas and Histone Modification In Gastr...mentioning
confidence: 99%